Distributional Update of Alsophila cuspidata (Kunze) Conant from Paraguay, and New Synonymy - Marquez, Gonzalo Javier (2011)
Based on morphological evidence and distribution, A. cuspidata is excluded from Paraguay. The close species, A. sternbergii, is considered to be present there, and Cyathea hassleriana H.Christ set as its synonymy.